Health Data Access Bodies under the European Health Data Space – A technocratic colossus or rubber stamp forum? - Paul Quinn (Technology and Regulation)
The proposal for a European Health Data Space (EHDS) has sparked extensive discourse, weighing the potential benefits for healthcare and innovation against concerns over privacy and societal impacts. At the heart of this discussion are the Health Data Access Bodies (HDABs), tasked with managing the reuse of secondary health data within the EHDS framework. This article delves into the formidable challenges facing HDABs, suggesting that the complexity and volume of data access requests may overwhelm their capacity. Ensuring compliance with EHDS regulations, GDPR provisions, and ethical standards presents a multifaceted challenge. The author argues that the expertise and efficiency required to navigate these complexities could strain HDAB resources and capabilities. Furthermore, the anticipated surge in data access requests may exacerbate these challenges, potentially compromising HDAB effectiveness. Consequently, there is a pressing need for a pragmatic approach to delineating HDAB responsibilities to ensure their ability to fulfill their role competently. By addressing these concerns, the EHDS can uphold individual rights, promote societal welfare, and foster trust in its overarching objectives.